Kajian Nilai-nilai Toleransi dan Gotong Royong Pada Permainan Tradisional di Kabupaten Sumenep - Salamet Wahedi; Mufti Syaifuddin; Hodairiyah (LPTNU Sumenep, 2024)
The existence of traditional games has indirectly shown the public the cultural results of a community group. Traditional games are a reflection of people's behavior in building their civilization. Remembering that traditional games have a basis in local culture or local wisdom that exists in the community itself. Traditional games, also known as folk games, are a recreational activity that not only aims to entertain oneself, but also as a tool to maintain social relationships and comfort in society. It is correct to say that play is a necessity for children, so that children gain value and progress in the development of daily life. Through traditional games, the values ​​of tolerance are introduced and instilled in individuals. Instilling the values ​​of tolerance through traditional games will be fun and not boring. The terminology